Does financial education enhance financial preparedness? Evidence from a natural experiment in Singapore. (15th August 2017) - BARUA, RASHMI; KOH, BENEDICT; MITCHELL, OLIVIA S.
Abstract: We evaluate how financial education provided to college students influenced their financial knowledge and planning in a quasi-experimental setting where we control for student motivation to enroll in the course. Using a difference-in-difference strategy, we show that financial education led to an increase in financial knowledge and planning. Specifically, we find that financial education improved students' financial knowledge score by 11%, and financial planning score by 16%. No statistically significant effects are detected for student levels of financial prudence, discipline, or outcomes related to credit card usage.